Effect of disease modifying agents on the lipid profiles of patients with rheumatoid arthritis. Issue 6 (1st June 1997) - Munro, R; Morrison, E; McDonald, A G; Hunter, J A; Madhok, R; Capell, H A
Abstract : OBJECTIVE: To determine the effect of intramuscular gold and oral hydroxychloroquine(HCQ) on the lipid profile of patients with rheumatoid arthritis (RA). METHOD: A prospective randomised clinical trial of 12 months' duration was performed in 100 RA patients. Data on clinical and laboratory parameters of disease activity, and fasting serum lipid samples was collected at baseline and at three monthly intervals over one year. RESULTS: The expected second line response was seen with no significant difference in efficacy between the groups at 12 months. The HCQ group had a significant overall improvement in their lipid profile while there was a trend for lipid profiles in the gold group to worsen. CONCLUSIONS: HCQ is an effective second line agent that has beneficial effects on serum lipids. This should be taken into account when choosing a disease modifying anti-rheumatic drug in patients who suffer from RA and who have significant cardiovascular risk factors.